The Involvement of State Officials in the 2024 Election Campaign Reviewed from the Siyasah Dusturiyah Perspective - Marina, Marina; Suganda, Delfi; Reza, T. Surya (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2024)
Elections are a democratic activity where every citizen has the right to directly elect leaders, people's representatives, and government officials for future leadership in a country. Apart from that, elections also become a stage for political contestation and become a democratic party in a democratic country. However, during the election, there were still many violations of the rules committed by several people. One of the rules that is often violated in organizing elections is during the campaign. This violation took the form of involvement of state officials in carrying out the campaign. In the 2024 Election, precisely during the campaign process, there are state officials who take part in the campaign, the state official who participates in the campaign is the Minister of Trade of the Republic of Indonesia. Basically, state officials are allowed to campaign but must fulfill several provisions, one of which is taking leave outside the state's responsibility and not being able to use state facilities other than accompanying the state official. However, the Minister of Trade of the Republic of Indonesia carried out a campaign outside the leave period that he had proposed. So his involvement in the campaign violated election administration. However, it is a shame that he did not receive strict sanctions from Bawaslu, as stipulated in the law, but the Minister of Trade of the Republic of Indonesia only received a strong warning from Bawaslu. This has also been prohibited in Siyasah dusturiyah, this is the same as not carrying out the mandate and abusing the authority that has been given.